2021
DOI: 10.1101/2021.11.02.466907
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell epigenetic analysis reveals principles of chromatin states in H3.3-K27M gliomas

Abstract: Cancer cells are highly heterogeneous, both at the transcriptional level and in their epigenetic state. Methods to study epigenetic heterogeneity are limited in their throughput and the information obtained per cell. Here, we adapted Cytometry by Time of Flight (CyTOF) to analyze a wide panel of histone modifications and chromatin regulators in primary tumor-derived lines of Diffused Intrinsic Pontine Glioma (DIPG). DIPG is a lethal pediatric brain cancer, driven by a mutation in histone H3 leading to substitu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 84 publications
1
5
0
Order By: Relevance
“…Using a custom-designed antibody panel for Epigenetic-focused CyTOF (EpiTOF) 80,81 (see Table S1), we performed high-dimensional phenotypic classification of single cells from five PyMT tumors from 3.5-month-old female mice. Including known markers of cell differentiation and identity [82][83][84][85][86] in the CyTOF panel enabled to assign of the tumor epithelial cells to subpopulations representing different phenotypic states: luminal progenitors ("lumP"), mature luminal ("luminal"), and a small but discrete subpopulation displaying molecular features that are commonly associated with a basal-like state ("basallike") (Fig S1a), as well as nonepithelial tumor-associated cells such as fibroblasts and immune cells.…”
Section: Resultsmentioning
confidence: 99%
“…Using a custom-designed antibody panel for Epigenetic-focused CyTOF (EpiTOF) 80,81 (see Table S1), we performed high-dimensional phenotypic classification of single cells from five PyMT tumors from 3.5-month-old female mice. Including known markers of cell differentiation and identity [82][83][84][85][86] in the CyTOF panel enabled to assign of the tumor epithelial cells to subpopulations representing different phenotypic states: luminal progenitors ("lumP"), mature luminal ("luminal"), and a small but discrete subpopulation displaying molecular features that are commonly associated with a basal-like state ("basallike") (Fig S1a), as well as nonepithelial tumor-associated cells such as fibroblasts and immune cells.…”
Section: Resultsmentioning
confidence: 99%
“…The antibody we have used in our study for the H3K27M mutation is commonly used in a reliable manner in routine diagnostic setting (4). Moreover, the same antibody, custom-conjugated has been used in a recently published work that, by employing the CyTOF technology, has investigated the epigenetic rearrangements due to H3K27M alteration in a panel of DMG-H3K27M mutant cell lines (68). Interestingly, Harpaz et al, have demonstrated the existence of two epigenetically distinct subpopulations in DMG-H3K27M mutant cell lines and suggest that these differences mirror the heterogeneous expression of the H3K27M oncohistone (68).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the same antibody, custom-conjugated has been used in a recently published work that, by employing the CyTOF technology, has investigated the epigenetic rearrangements due to H3K27M alteration in a panel of DMG-H3K27M mutant cell lines (68). Interestingly, Harpaz et al, have demonstrated the existence of two epigenetically distinct subpopulations in DMG-H3K27M mutant cell lines and suggest that these differences mirror the heterogeneous expression of the H3K27M oncohistone (68). While we confirmed that the antibody anti-H3K27M can be used in a robust manner, unfortunately, the H3.3G34R antibody, which was custom-conjugated and used for CyTOF analysis for the first time in this study, did not prove accurate, due to its poor specificity.…”
Section: Discussionmentioning
confidence: 99%
“…By applying CyTOF to blood immune cells, recent studies showed increased epigenetic heterogeneity associated with ageing [ 52 ] and following vaccination [ 53 • ]. Similar high dimensionality profiling of pediatric gliomas driven by H3-K27M revealed two distinct epigenetic subpopulations, driven by the expression levels of the oncohistone, with functional consequences to the tumor biology [ 54 ].…”
Section: High-resolution Methods To Profile the Combinatorial Epigenomementioning
confidence: 99%